Diagnostic efficacy of high-resolution computed tomography findings in patients of chronic suppurative otitis media atticoantral type - Gajjar, Nikki; Bhalodiya, Neena; Bhadania, Simple (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: High resolution computed tomography (HRCT) provides information about anatomy and pathology of temporal bone and middle ear cleft, thus becoming important imaging modality in diagnosis and pre-operative planning in patients of chronic suppurative otitis media (attico-antral) CSOM (AA) type. The aim of study was to study disease extension and plan surgery accordingly in patients of CSOM (AA) and to study correlation between the HRCT findings and intra-operative findings of CSOM (AA) like soft tissue density mass, ossicular chain erosion, facial canal dehiscence, semi-circular canal erosion. Methods: Study of 70 patients clinically diagnosed of having CSOM (AA) in period between August 2018 to March 2020 was done at Sola civil hospital, Ahmedabad. All patients were advised HRCT temporal bone except those who had contraindications to CT scan, analysed and operated. Pre-operative CT-scan findings and intra-operative findings were compared for statistical analysis. Results: Soft tissue density was found in 100% of cases on HRCT temporal bone. Bony erosion seen in 25% of cases. 90% showed ossicular erosion. Lateral semi-circular canal fistula was observed in 10% of cases with facial canal dehiscence in 10% of cases. Intra-operative findings showed accuracy of HRCT in detecting soft tissue density to be 100%; bony erosion was observed in 25% cases. 10% patients had lateral semi-circular canal fistula. Facial canal dehiscence was seen in 15% cases. Conclusion: HRCT has proved quite useful and reliable to identify the disease extension before surgery and plan surgery accordingly.